Contributions to one health approach to solve geogenie health issues - Chandrajith, Rohana; Barth, Johannes (wiley, 2023)
"One Health" is a concept that developed during the last two decades. It considers the health of humans, animals, and the ecosystem as a whole, where health issues cannot be tackled in isolation. The geogenic environment that is represented by the lithosphere, hydrosphere, and atmosphere is an important component and has direct links with noncommunicable chronic health issues among humans and animals. For instance, excess or lack of particular elements, such as fluoride in the geogenic environment, plays an important role in health as exemplified by dental and skeletal fluorosis. Other examples include the consumption of arsenic-contaminated water that can lead to cancer and high background radiation caused by uranium and radon. In this chapter, we provide an overview and highlight the importance of the geochemistry of the living environment and its contribution to the "One Health" concept.
CRIS-Team Scopus Importer:2023-07-21
Keywords: Dental and skeletal fluorosis; Dose-response relationship; Medical geology; Radon and health